Safety perception of stairs with integrated lighting. (December 2019) - Van de Perre, Laurens; Danschutter, Stefan; Janssens, Kim; Hanselaer, Peter; Dujardin, Marc; Smet, Kevin A.G.; Ryckaert, Wouter R.
Abstract: Fall accidents on stairs occur regularly and can cause serious injuries. The risk of accidents increases with age. Many contributing factors are related to stair accidents such as personal and environmental factors. The presented research focuses on the influence of several lighting conditions on the perceived safety of a staircase in a dark environment. A mock-up staircase was built and the lighting consisted of a LED strip in the handrail illuminating the staircase and two LED strips in each stair nose mounted upwards and downwards. In total, 30 elderly observers evaluated the staircase on how safe they perceived the lighting scenes in order to descend the stairs. Results show an increased perceived safety when using the LED strip in either the handrail or the stair nose illuminating downwards. An increased intensity of the LED strip illuminating upwards resulted in a substantial decrease of the perceived safety. A model that accurately predicts the perceived safety is proposed. Input parameters of the model are the measured luminance values of the staircase. The model could also be used to design a staircase with an appropriate luminance distribution. Highlights: Controlled experiment on safety perception of stairs with integrated lighting. Experiment with 30 elderly in a night-time situation with a top-to-bottom point of view. Increased upward luminous intensity negatively impacts perceived safety. Higher average luminance on steps results in higher perceived safety. Presented luminance model accurately predicts perceived safety.